الأبعاد الاقتصادية والسياسية لخط سكك حديد أديس أبابا -جيبوتي (دراسة جغرافية) - أبو بكر موسى سعد أبو خشيم; أبو عبيدة عبدالقادر حويل (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd, 2025)
دراسة  الأبعاد الاقتصادية والسياسية لخط سكك حديد أديس أبابا – جيبوتي (دراسة جغرافية) ذات أهمية كبرى لما له من نجاحات تنموية على المستويين الاقتصادي والسياسي لكلتا الدولتين . وخط سكك حديد أديس أبابا – جيبوتي ليس وليد اليوم ، فهو يمتد في أعماق التاريخ لمدة طويلة ، حيث بدأت الأعمال التمهيدية لإنشاء هذا الخط بين الدولتين عام 1897م ، واستغرق بناؤه 20 عام ، حيث اكتمل البناء وتم الإفتتاح رسمياً في 6 يونيو 1917م ، وهذا الخط توقف عام 2006. تم الشروع في بناء الخط الجديد بين عامي 2011 و 2016 و بدأ التشغيل التجريبي للخط في شهر أكتوبر عام 2016، وتم افتتاح القسم الإثيوبي في 5 أكتوبر 2016، وأعلن عن اكتمال الخط الحديدي في 10 يناير 2017، وأقيم الاحتفال في محطة ناغاد للسكك الحديدية في القسم الجيبوتي ، ويطلق عليه الخط الكهربائى . ويلعب خط سكك حديد أديس أبابا – جيبوتي دوراً مهماً فى حركة نقل الركاب والبضائع ، وخاصة حركة الصادرات والواردات الإثيوبية ، وهذا الخط يعتبر المنفذ البحري الوحيد لإثيوبيا الآن .      Studying the economic and political dimensions of the Addis Ababa-Djibouti railway line (geographical study) is of great importance because of its development successes at the economic and political levels for both countries. The Addis Ababa-Djibouti railway line is not new today, as it extends deep into history for a long time, as the preliminary work for establishing this line between the two countries began in 1897, and its construction took 20 years, when construction was completed and it was officially opened on June 6, 1917, and this line stopped. 2006. Construction of the new line began between 2011 and 2016, and trial operation of the line began in October 2016. The Ethiopian section was opened on October 5, 2016, and the completion of the railway was announced on January 10, 2017. The celebration was held at the Nagada railway station on the section. Djibouti, and it is called the electric line. The Addis Ababa-Djibouti railway line plays an important role in the movement of passengers and goods, especially the movement of Ethiopian exports and imports, and this line is considered the only sea port for Ethiopia now.